Sistem Informasi Manajemen Obat Berbasis Web Studi Kasus : Klinik Pratama Universitas Pahlawan Tuanku Tambusai - Mahendra, Ogta Fio; Gusman, Deddy; Munti, Novi Yona Sidratul (PT Pustaka Cendekia Group, 2023)
Tuanku Tambusai University of Heroes Primary Clinic is located at Jalan Tuanku Tambusai. The Hero University Primary Clinic provides general examination services such as dental examinations, emergency departments and others. The process is still manual and there are no reminders for drug stocks and expired dates that often cause losses for pharmacies. With these problems, a well-organized management information system is needed. The system uses laravel with the system using the Blackbox testing method. From the results of the test, the system runs smoothly 100% without any bugs in the system. This website makes it easier for pharmacists to manage drug data at the Hero University primary clinic. This website can also help doctors and pharmacists in various ways such as knowing the amount of drug stock available and also helping doctors to send prescriptions to pharmacists. the database is xampp, the development method uses the prototype method. In this study the authors used a descriptive research method with a qualitative approach.